Hubungan Rasio Lingkar Pinggang Pinggul (RLPP) dengan Kadar Gula Darah pada Pegawai di Puskesmas Sakti Pidie - Nunung Sri Mulyani; Novia Rita (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
Obesity risk of developing the degenerative disease is eight times larger than the nutritional status normal.Prevalensinya increased not only in developed countries but also in developing countries, including Indonesia. Prevalence in Aceh on the nutritional status obtained meager 11.1%, 61.1% normal weight and 11.6% were obese as much as 16.3%. Insulin resistance happens in the obese group then lead to reduced insulin, causing glucose to enter the cells difficult. This situation ends to elevated levels of glucose in the blood. The aim of research to measure the relationship waist-hip ratio (waist-hip ratio) with blood sugar levels in employees in Puskesmas Sakti Pidie 2016. This research is descriptive analytic conducted cross-sectional. The number of samples 60 people. Data collected by measuring waist circumference, hip circumference, and blood sugar levels respondents. Data analysis statistical test Spearman Rank Correlation. The results of the study the majority of respondents have an abnormal waist-hip ratio of 93.3%, and most respondents had a low blood sugar level of 75%. Spearman Rank Correlation Analysis Results in Waist Hip Ratio (waist-hip ratio) with Blood Sugar Levels in Employees that have a weak correlation (rs = 0.024) and a positive pattern, the greater Waist Hip Ratio, the higher the blood sugar levels. Statistical test results obtained p = 0.856 means that there is no relationship Waist Hip Ratio with Blood Sugar Levels in Pidie Sakti Employees in the health center. Conclusion: There lies an association between the ratio of waist to hip circumference (waist-hip ratio) with blood sugar levels in employees in Puskesmas Sakti Pidie. Keywords : Waist hip ratio, blood sugar levels